The Outcome of Neutrophil-T Cell Contact Differs Depending on Activation Status of Both Cell Types - Minns, Danielle; Smith, Katie J.; Hardisty, Gareth; Rossi, Adriano G.; Gwyer Findlay, Emily (Frontiers in Immunology, 2021)
Neutrophils and T cells exist in close proximity in lymph nodes and inflamed tissues during health and disease. They are able to form stable interactions, with profound effects on the phenotype and function of the T cells. However, the outcome of these effects are frequently contradictory; in some systems neutrophils suppress T cell proliferation, in others they are activatory or present antigen directly. Published protocols modelling these interactions in vitro do not reflect the full range of interactions found in vivo; they do not examine how activated and naïve T cells differentially respond to neutrophils, or whether de-granulating or resting neutrophils induce different outcomes. Here, we established a culture protocol to ask these questions with human T cells and autologous neutrophils. We find that resting neutrophils suppress T cell proliferation, activation and cytokine production but that de-granulating neutrophils do not, and neutrophil released intracellular contents are pro-activatory. Strikingly, we also demonstrate that T cells early in the activation process are susceptible to suppression by neutrophils, while later-stage T cells are not, and naïve T cells do not respond at all. Our protocol therefore allows nuanced analysis of the outcome of interaction of these cells and may explain contradictory results observed previously.